Bio-evaluation of Untapped Alkaloids from Vinca minor Enriched by Methyl-jasmonate-induced Stress: an Integrated Approach - El-Senduny, Fardous F.; Elgazar, Abdullah A.; Alwasify, Heba Allah; Abed, Alaa; Foda, Mohamed; Abouzeid, Sara; Lewerenz, Laura; Selmar, Dirk; Badria, Farid (Planta Medica, 2023)
The low amount of metabolites isolated from natural products is one of the challenges preventing their biological evaluation. The modulation of biosynthetic pathways by stimulating stress-induced responses in plants was proven to be a valuable tool for diversification of already known natural products. Recently, we reported the dramatic effect of methyl jasmonate (MeJA) on Vinca minor alkaloids distribution. In this study, three compounds identified as 9-methoxyvincamine, minovincinine, and minovincine are successfully isolated in good yield and subjected to several bioassays based on a network pharmacology study. The extracts and isolated compounds show weak to moderate antimicrobial and cytotoxic activities. Also, they are found to significantly promote wound healing in scratch assay, and transforming growth factor-β (TGF-β) modulation is suggested to be the potential pathway based on bioinformatic analysis. Hence, Western blotting is used to assess the expression of several markers related to this pathway and wound healing. The extracts and isolated compounds are able to increase the expression of Smad3 and Phosphatidylinositol-3-kinase (PI3K), while downregulating the levels of cyclin D1 and the mammalian target of rapamycin (mTOR) except for minovincine, which increases the mTOR expression, inferring that it might act through a different mechanism. Molecular docking is used to give insights on the ability of isolated compounds to bind with different active sites in mTOR. Collectively, the integrated phytochemical, in silico, and molecular biology approach reveal that V. minor and its metabolite could be repurposed for the management of dermatological disorders where these markers are dysregulated, which opens the gate to develop new therapeutics in the future.
Keywords: Vinca minor; Apocynaceae; vinca alkaloids; chemical elicitor; in silico pharmacology; wound healing